Elicitins, proteinaceous elicitors of plant defense, are a new class of sterol carrier proteins - Mikes, V; Milat, M L; Ponchet, M; Panabières, F; Ricci, P; Blein, J P (Biochemical and biophysical research communications, 1998)
Some phytopathogenic fungi within Phytophthora species are unable to synthesize sterols and therefore must pick them up from the membranes of their host-plant, using an unknown mechanism. These pseudo-fungi secrete elicitins which are small hydrophilic cystein-rich proteins. The results show that elicitins studied interact with dehydroergosterol in the same way, but with some time-dependent differences. Elicitins have one binding site with a similar strong affinity for dehydroergosterol. Using a non-steroid hydrophobic fluorescent probe, we showed that phytosterols are able to similarly bind to elicitins. Moreover, elicitins catalyze sterol transfer between phospholipidic artificial membranes. Our results afford the first evidence for a molecular activity of elicitins which appears to be extracellular sterol carrier proteins. This property should contribute to an understanding of the molecular mechanism involved in sterol uptake by Phytophthora. It opens new perspectives concerning the role of such proteins in plant-microorganism interactions, since elicitins trigger defence reactions in plants.
Keywords: fluorescenční barviva; kinetika; rostliny; biologický transport; fytosteroly; fluorescenční spektrometrie; Protein Binding; Carrier Proteins; Fluorescent Dyes; Biological Transport; ergosterol; fungální proteiny; Plants; naftalensulfonany; Naphthalenesulfonates; bílkoviny řas; Spectrometry, Fluorescence; Algal Proteins; Fungal Proteins; Ergosterol; Phospholipids; Binding Sites; Phytosterols; vazba proteinů; Kinetics; fosfolipidy; transportní proteiny; vazebná místa; Phytophthora